Building a framework for integrated risk management of complex projects: The case of a major distribution network investment - Houghton, T.; Ackermann, Fran; Howick, S.; Quigley, J.; Walls, L. (2013)
With the introduction of intermittent renewable generation, distributed energy storage and demand side management, distribution network developments are becoming ever more complex. Northern Isles New Energy Solutions (NINES), led by Scottish and Southern Energy Power Distribution (SSEPD) and supported by Ofgem, aims to incorporate all of these elements into a combined active network management (ANM) scheme. This paper describes a risk management framework that has been developed to assist the managers of the NINES project deal with the multi-faceted challenges presented by large and complex projects. The process combines two parallel but interwoven activities; the first engages a range of stakeholders, using a group decision support system to facilitate the surfacing of risks and their ramifications, in a causal risk mapping process, while the second engages with the SSEPD team to elicit expert judgement regarding specific uncertainties so as to understand the likelihood of particular risks occuiring. This in mm allows the consequences of the risks to be evaluated quantitatively and the implications to be more fully assessed by the project management team through a decision tree (DT) approach. While developed here specifically for NINES, the fiwnework has potential across a range of complex project management situations.